Smart concrete - Dhir, Ravindra K.; Paine, Kevin A. (ICE themes., 2019)
In defining smart concrete as concrete that is capable of responding automatically to the actions imposed upon it, research has sought to develop concrete that is stronger, more sustainable and resilient. This assists the construction industry with improved whole life performance of concrete structures. With ICE Publishing material collated from key subject matter experts working in the field of concrete, ICE Themes Smart Concrete reveals how the field has evolved and shows how smart concrete may be used in the future. It offers readers with a view of the key developments that have impacted the evolution of smart concrete such as self-curing concrete, self-healing concrete, cementitious materials, and sensor monitoring.